TAFSIR AL-HIJRI: Potret Tafsir Syafahi di Indonesia - Ahmad Jauhari Abbas; Rijalu Gunawan; Fathurrosyid (Jurnal Studi Qur'an dan Tafsir, 2022)
Abstract Tafsir Al-Hijri is an interpretation work that has adorned the world of interpretation in Indonesia and served as a bridge for people to understand the content of the Qur'an. This interpretation presents itself as a solution to the problems faced by people. Therefore, the methodology and systematics of writing this tafsir are worth investigating. This research aims to map the methodology of interpreting Tafsir Al-Hijri, including its physiological data, origins, methods, and related aspects. Qualitative research methods with an interpretive approach were used to review the interpretation and provide an assessment. The data analysis method used the Miles and Huberman model, which involves data reduction, data display, and conclusion drawing. The research reveals that Tafsir Al-Hijri is a non-academic tafsir that originated from "Shafahi" interpretation (delivered orally) and was later documented. Keywords: Tafsir Syafahi, methodological mapping, Indonesian tafsir